The coexistence of acorns with different maturation patterns explains acorn production variability in cork oak. - Pons, Josep; Pausas, Juli G. (Oecologia, 2012)
In dry areas such as Mediterranean ecosystems, fluctuations in seed production are typically explained by resource (water) availability. However, acorn production in cork oak (Quercus suber) populations shows a very low relationship to weather. Because cork oak trees produce acorns with different maturation patterns (annual and biennial), we hypothesized that acorn production in coexisting individuals with a different dominant acorn maturation type should respond differently to climatic factors and that disaggregating the trees according to their acorn-maturation pattern should provide a more proximal relation to weather factors. We assessed acorn production variability in fragmented cork oak populations of the eastern Iberian Peninsula by counting the total number of acorns in 155 trees during an 8-year period. An initial assessment of acorn production variability in relation to weather parameters yielded very low explained variance (7%). However, after the trees were grouped according to their dominant acorn maturation pattern, weather parameters were found to account for 44% of the variability in acorn crops, with trees with annual acorns exhibiting mast fruiting in years with reduced spring frost and shorter summer droughts and trees with biennial acorns showing the opposite pattern. Thus, conditions that negatively affect annual production could be beneficial for biennial production (and vice versa). The results highlight the importance of the resource-matching hypothesis for explaining acorn production in Quercus suber and suggest that different seed maturation types within a population may allow the species to deal with highly variable weather conditions. They also emphasize the importance of understanding acorn maturation patterns for interpreting masting cycles.
The following values have no corresponding Zotero field: accession-num: 22246473
Keywords: biomass; Evergreen oaks; Fruit; Fruit: growth & development; Hypothesis; Masting; Mediterranean Region; Mediterranean woodlands; Quercus; Quercus suber; Quercus: growth & development; Weather